SAFETY OF PREGNANT WOMEN DURING THE COVID-19 PANDEMIC BY USING THE TELEHEALTH APPLICATION: A SYSTEMATIC REVIEW - Iva Satya Ratnasari; Indah Rahmaningtyas; Finta Isti Kundarti (Indonesian Midwifery and Health Sciences Journal, 2022)
Abstract Introduction: The COVID-19 pandemic has affected the routine access of pregnant women to do ANC visits at health facilities. Various midwifery services have changed and developed through telehealth. Objectives: Analyze the effect of telehealth applications on pregnant women's safety during the COVID-19 pandemic through a systematic review. Methods: This study used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The literature was carried out using keywords and Boolean operators through Pubmed, ProQuest, Science Direct, and Wiley Library databases with the publication year from December 2019 to January 2022. Results: 5 articles met the inclusion criteria. Two studies were conducted in the United States. Studies were also conducted in Australia, Poland, and China. The use of telehealth was safe to apply to pregnant women to carry out pregnancy care during the COVID-19 pandemic because telehealth services increase patient access to health care providers. A total of 3 articles described that the use of telehealth compared to general face-to-face care did not lead to worse pregnancy outcomes and could reduce the spread of the COVID-19 virus among pregnant women. Conclusion: The use of telehealth was safe for pregnant women to carry out pregnancy care during the COVID-19 pandemic and beyond. Although the use of telehealth had limitations such as difficulties in conducting a comprehensive physical examination and the possibility of obstacles in the use of technology, telehealth could continue to be developed in addition to and complement in-person visits. Further research could be done by minimizing bias in retrospective studies. Keyword : COVID-19, Patient safety, Pregnancy, Telehealth